2007
DOI: 10.1124/dmd.107.015958
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profile of [14C]Bendamustine in Rat Urine and Bile: Preliminary Structural Identification of Metabolites

Abstract: ABSTRACT:Bendamustine, a bifunctional alkylating agent, is currently in clinical trials for the treatment of hematological and other malignancies. Although it has been used in the former East Germany for more than 30 years, very limited information is available on its biotransformation. The objective of this investigation was to obtain information on the structures of metabolites excreted into rat urine and bile to understand the metabolic fate of bendamustine in vivo. Metabolites of [14 C]bendamustine hydroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 6 publications
5
18
0
Order By: Relevance
“…The identification was supported by the highresolution m/z value and by the major product ions 258.1232 (Ϫ18.0104 Da, loss of water), 230.1283 (Ϫ46.0053 Da, loss of carboxyl moiety), and 217.0972 (Ϫ59.0364, loss of aminoacetaldehyde), which are consistent with those reported for this compound in rat urine (Chovan et al, 2007).…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…The identification was supported by the highresolution m/z value and by the major product ions 258.1232 (Ϫ18.0104 Da, loss of water), 230.1283 (Ϫ46.0053 Da, loss of carboxyl moiety), and 217.0972 (Ϫ59.0364, loss of aminoacetaldehyde), which are consistent with those reported for this compound in rat urine (Chovan et al, 2007).…”
Section: Resultssupporting
confidence: 76%
“…The types of metabolites that were observed in this study were generally consistent with those reported previously for rat (Chovan et al, 2007). The most abundant metabolite in rat urine and bile was a mercapturic acid conjugate of bendamustine, corresponding with Met22 in this study.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations